Pengaruh Pengetahuan Kewirausahaan dan Sosial Media terhadap Minat Berwirausaha: (Pada Generasi Muda dan Milenial di Sidoarjo) - Mita Rusdiana; Iswati Iswati; Anis Fitriyasari; Arief Widjadmoko (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This study wants to find out more about "The Influence between Entrepreneurial Knowledge and Social Media with Entrepreneurial Interest" in accordance with the main problem raised, namely the influence of knowledge about entrepreneurship and social media on entrepreneurial interest in young generation in the Sidoarjo. The background of this research on entrepreneurial interest is that there are still many young who prefer to work as employees in a company, while they also have opportunities in entrepreneurship as an additional income or can be made as the main job. With the social media knowledge that the younger generation has, it can support their business. The purpose of this study is to find out: how the influence between entrepreneurial knowledge and social media on entrepreneurial interest. The method used in this study is a correlational method that aims to measure the relationship between various variables. Meanwhile, to support this research obtained from interviews, observations, making google forms. The target in this study is young generation in the Sidoarjo area, a sample taken by 100% of the population. After conducting several ways of research or data collection, it will be calculated to determine the results. The conclusion of this study is that there is a relationship between entrepreneurial knowledge and social media knowledge in supporting the business itself, so that it can attract the interest of the younger generation in entre.